A core-shell structured PAAS-PNIPAAm hydrogel material for environmental water collection
By adopting a core-shell structure, PAAS-PNIPAAm hydrogel material, combined with ultraviolet radiation method and the use of polydopamine nanoparticles, the problem of poor hygroscopic material in low humidity environments is solved, and efficient water collection and Photothermal conversion performance.
Patent Information
- Application Number
- CN202210664126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-06-14
AI Technical Summary
The existing hygroscopic materials have poor hygroscopic properties in low humidity environments and low water evaporation and collection efficiency, which limits their application in atmospheric water traps.
The PAAS-PNIPAAm hydrogel material with core-shell structure was prepared by ultraviolet radiation method. The shell layer is a sodium polyacrylate hydrogel with excellent hygroscopic properties, and the core layer is a large pore hydrogel with rapid water release of temperature-sensitive PNIPAAm and coat polydopamine nanoparticles on the surface to improve photothermal conversion performance.
Under humidity conditions as low as 30%, the water adsorption capacity is as high as 0.66g/g-1. The surface temperature of the material can quickly rise to 70℃ within 3 minutes at 1 sunlight intensity, greatly improving the water collection efficiency.
Smart Images

Figure CN114940799B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous adsorbent materials and environment and energy, and in particular to a PAAS-PNIPAAm hydrogel material with a core-shell structure for environmental water collection. Background Art
[0002] At present, water shortage has become one of the most challenging problems threatening human life. According to the latest report released by the World Meteorological Organization, the groundwater level of the earth has dropped at a rate of 1 cm per year in the past 20 years. If it continues, the number of people who lack water in the world is expected to reach 5 billion by 2050. This will have a major impact on global water security. Therefore, in response to this serious problem, some effective measures have been proposed to capture and utilize the limited fresh water on the earth. For example, seawater desalination, atmospheric water harvesting and sewage treatment. Considering that environmental water is a huge reservoir of clean water resources, accounting for about 10% of the water in global lakes, atmospheric water harvesting has attracted a lot of research interest and has become one of the alternative and promising methods for producing fresh water. In this case, hygroscopic materials based on surface water adsorption, such as hygroscopic salts, molecular sieves, silica gel and polymer desiccants, can be used as hygroscopic agents in a wide humidity range. However, hygroscopic materials designed for moisture capture have a strong interaction with water, which greatly hinders the release of water and weakens their use as atmospheric water capturers. Afterwards, researchers gradually used nanoporous materials such as metal-organic frameworks (MOFs) and covalent-organic frameworks (COFs) with excellent hygroscopic properties for environmental water collection. However, their low yield, high price, and long time consumption limited their application in environmental water collection.
[0003] For example, Chinese patent CN113501995 A discloses "a natural polymer-based atmospheric water collection material and its preparation method", which uses natural polymers as a matrix and cross-links to obtain a structural atmospheric water collection material with a hollow interior and a large number of macropores and micropores on the surface. The natural polymer used in its preparation process is a natural polymer substance with a polysaccharide main chain and a hydrophilic side chain. For example, Chinese patent CN113426416 A discloses "a MOFs material with high-efficiency water collection performance, its preparation method and air water collection application", which is achieved by weighing a tetracarboxylic acid ligand and a zirconium salt with a hydrophilic functional group into a reactor, adding an anhydride solution, ultrasonicating for 15 minutes to obtain a uniform turbid liquid, and then adding an organic acid to ultrasonically homogenize, placing the reactor in an oven at 110-130 degrees to react for at least 24 hours, and then washing the obtained precipitate with ethanol, and drying in the air to obtain a homogeneous porous environmental water collection material.
[0004] Hydrogel is a material with strong hydrophilicity and good three-dimensional porous structure, which shows great advantages in water absorption and transportation. At the same time, hydrogel can reduce the evaporation enthalpy required for water evaporation, so the energy required for dehydration will be lower than that of previous hygroscopic materials (zeolite, silica gel, molecular sieve, etc.). In addition, some hydrogels also have special stimulus response properties, such as poly N-isopropylacrylamide (PNIPAAm), which can further improve the dehydration capacity of hydrogels. The above advantages ensure that the hydrogel can continuously transport water to the surface and evaporate quickly, so that the hydrogel has high water retention and good recyclability, and becomes a very promising environmental water collection material. Therefore, the present invention discloses a hydrogel environmental water collection material with a core-shell structure, which uses a sodium polyacrylate (PAAS) hydrogel with excellent hygroscopic swelling properties as a shell layer to absorb and transmit water at night. Thermosensitive PNIPAAm is used as the core layer to quickly collect the water collected at night under light. In addition, we also use polydopamine (PDA) nanoparticles as light-absorbing materials. Once the core-shell hydrogel is exposed to natural sunlight, the polydopamine nanoparticles absorb sunlight and quickly heat the hydrogel to above the LCST (lower critical phase transition temperature). As the hydrogel phase changes, it changes from a hydrophilic state to a hydrophobic state, and clean liquid water is collected as liquid and vapor. This core-shell structure design with different pore sizes and mutual synergy can not only speed up the collection of moisture at night, but also speed up the collection of moisture under the irradiation of sunlight. Summary of the invention
[0005] The purpose of the present invention is to provide a core-shell PAAS-PNIPAAm hydrogel material for environmental water collection. The hydrogel environmental water collection material with a core-shell structure is prepared by ultraviolet irradiation method to solve the problems of poor hygroscopic performance of the adsorption material in a low humidity environment, water evaporation, and low collection efficiency.
[0006] The technical solution of the present invention is:
[0007] Step 1: Prepare PNIPAAm hydrogel by irradiating a mixed aqueous solution of NIPAAm, sodium carboxymethyl cellulose (CMC), a crosslinker and a photoinitiator under ultraviolet light under low temperature conditions to obtain PNIPAAm hydrogel;
[0008] Step 2: Prepare PAAS-PNIPAAm hydrogel by placing the PNIPAAm hydrogel in a hollow column mold in a culture dish, and then injecting a PAA mixed aqueous solution containing acrylic acid, a photoinitiator, a crosslinker, and dimethyl sulfoxide into the culture dish. After ultraviolet light irradiation, a core-shell structure hydrogel is obtained;
[0009] Step 3, preparing a core-shell structure PAAS-PNIPAAm hydrogel environmental water collection material, first preparing a core layer poly N-isopropylacrylamide (PNIPAAm) macroporous hydrogel, then coating a layer of open-pore structured small-pore sodium polyacrylate (PAAS) hydrogel on the surface of the PNIPAAm hydrogel to obtain a PAAS-PNIPAAm hydrogel, and finally coating polydopamine (PDA) nanoparticles on the surface of the PAAS-PNIPAAm hydrogel, and immersing it in a LiCl solution to prepare a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection;
[0010] Furthermore, the PNIPAAm hydrogel was prepared as described in step 1, wherein the monomer NIPAAm, the photoinitiator α-ketoglutaric acid and the crosslinker N,N-methylenebisacrylamide were dissolved in 10 mL of deionized water at 20°C, and then sodium carboxymethyl cellulose was added to the above solution and magnetically stirred for 4 hours to obtain a NIPAAm mixed aqueous solution. The uniformly mixed solution was slowly injected into a 6 cm culture dish, and the culture dish was moved to a sealed container. After N2 was introduced for 20 minutes, it was placed under a 250 W ultraviolet lamp for irradiation for 40 minutes, and soaked in deionized water for 24 hours. The water was changed regularly to remove unreacted monomers and crosslinkers to obtain a PNIPAAm hydrogel.
[0011] Furthermore, in the NIPAAm mixed aqueous solution in step 1, the mass concentration of the required monomer NIPAAm is 2% to 10%; the mass concentration of the cross-linking agent is 1% to 5%; the mass concentration of the sodium carboxymethyl cellulose is 0.1% to 1%; and the mass concentration of the photoinitiator is 0.5%.
[0012] Furthermore, the PAAS-PNIPAAm hydrogel is prepared as described in step (2), wherein the monomer acrylic acid (AA), the photoinitiator α-ketoglutaric acid and the crosslinking agent N,N-methylenebisacrylamide are dissolved in a dimethyl sulfoxide-water (DMSO-H2O) mixed solution, and then the mixed aqueous solution is injected into a mold, and then the mold is slowly moved into a sealed container, N2 is introduced for 20 minutes, and then placed under a 250 W ultraviolet lamp for irradiation for 20 minutes, and the core-shell structure hydrogel is carefully taken out from the mold and immersed in deionized water for 24 hours until the unreacted monomer and DMSO are removed to obtain the PAAS-PNIPAAm hydrogel.
[0013] Furthermore, in step (2), the mass concentration of monomer AA in the sodium polyacrylate mixed aqueous solution is 0.5% to 3%; the mass concentration of the crosslinking agent is 2% to 12%; the volume ratio of dimethyl sulfoxide to water is 1:9 to 1:1; and the mass concentration of the photoinitiator is 0.5%.
[0014] Furthermore, in step (3), a core-shell structured PAAS-PNIPAAm hydrogel environmental water collection material is prepared by first preparing a core layer poly N-isopropylacrylamide (PNIPAAm) macroporous hydrogel, and then coating a layer of open-pore structured small-pore sodium polyacrylate (PAAS) hydrogel on the surface of the PNIPAAm hydrogel to obtain a PAAS-PNIPAAm hydrogel. Finally, polydopamine (PDA) nanoparticles are coated on the surface of the PAAS-PNIPAAm hydrogel, and the surface is immersed in a LiCl solution to prepare a core-shell structured PAAS-PNIPAAm hydrogel material for environmental water collection. The steps include: first, preparing a PAAS-PNIPAAm hydrogel according to step (2); then, adding the core-shell structure PAAS-PNIPAAm hydrogel to a pH=8.5, 50mM Tris-HCl buffer solution, and after fully swelling for 24 hours, immersing the sample again in a Tris-HCl buffer solution containing dopamine and 5mM CuSO4 / 19.6mM H2O2, and magnetically stirring for 4 hours; then, washing the sample with water overnight, and placing it in a freeze dryer for pre-freezing and freeze-drying to obtain a PAAS-PNIPAAm hydrogel; finally, immersing it in a LiCl solution for 24 hours, and drying the prepared PAAS-PNIPAAm hydrogel in an oven at 80°C for 3 days to obtain a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection.
[0015] Furthermore, in the Tris-HCl buffer solution in step (3), the dopamine concentration is 2 to 10 mg / mL; and the LiCl solution concentration is 0.1 to 0.6 g / mL.
[0016] The advantages of the present invention are:
[0017] The invention adopts environmentally friendly ultraviolet irradiation technology to prepare hydrogel environmental water collection materials, reduces the harm of chemical reagents (ammonium persulfate, sodium bisulfite) to the human body, and the ultraviolet preparation method simplifies the process flow and is environmentally friendly.
[0018] The present invention adopts a core-shell structure to design a hydrogel environmental water collection material. The shell layer is a small-pore sodium polyacrylate hydrogel with excellent hygroscopic and swelling properties, which is beneficial to the absorption and transmission of water at night. The core layer is a large-pore hydrogel with thermosensitive PNIPAAm that releases water quickly, which is beneficial to the rapid collection of water collected at night under light. In addition, we also use polydopamine as a light-absorbing material. Once the core-shell structure hydrogel is exposed to natural sunlight, PDA absorbs sunlight to quickly heat the hydrogel to above LCST. Due to the phase change of the hydrogel, it changes from a hydrophilic state to a hydrophobic state, and clean liquid water is collected as liquid and vapor. This core-shell structure design with different pore sizes and mutual synergy can not only speed up the collection of moisture at night, but also speed up the collection of moisture under the irradiation of sunlight. Under humidity conditions as low as 30%, the water adsorption capacity is still as high as 0.66gg -1 .
[0019] The water collection material obtained by the simple and green preparation method in the present invention has excellent photothermal conversion performance. Under the irradiation of 1 sun intensity, the surface temperature can quickly rise to 70°C within 3 minutes, which greatly improves the water collection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.
[0021] Figure 1 This is a surface SEM image of the PAAS hydrogel prepared in Comparative Example 2;
[0022] Figure 2 This is a surface SEM image of the PNIPAAm hydrogel prepared in Comparative Example 1;
[0023] Figure 3 This is a surface SEM image of the material prepared in Example 1 of a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection of the present invention;
[0024] Figure 4 The wettability of the material surface prepared in Example 1 of the core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection of the present invention;
[0025] Figure 5 The hygroscopic properties of the material prepared in Example 1 of the core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection of the present invention at different humidity levels;
[0026] Figure 6 The photothermal conversion performance of the material prepared in Example 1 of a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection of the present invention;
[0027] Figure 7 The water release performance of the material prepared in Example 1 of a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection of the present invention; DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the technical scheme of the present invention is further described below in conjunction with the accompanying drawings, embodiments and comparative examples. However, the present invention is not limited to the embodiments listed, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0029] First, the "embodiment 1" referred to herein refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. Secondly, the present invention is described in detail using a structural schematic diagram, etc. When describing the embodiment of the present invention in detail, for the sake of convenience, the schematic diagram will not be partially enlarged according to the general proportion, and the schematic diagram is only an example, which should not limit the scope of protection of the present invention. In addition, in actual production, a three-dimensional space of length, width and depth should be included.
[0030] In addition, the abbreviations mentioned in the present invention are all fixed abbreviations in the art, and some of the abbreviations are explained as follows: PNIPAAm: poly (N-isopropylacrylamide); PAAS: sodium polyacrylate; PDA: polydopamine; CMC: sodium carboxymethyl cellulose; DMSO: dimethyl sulfoxide; LCST: lower critical transition temperature; SEM: scanning electron microscope.
[0031] Embodiment 1
[0032] This embodiment prepares a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to the following steps:
[0033] Step 1: Preparation of nuclear layer PNIPAAm hydrogel
[0034] The core layer hydrogel was prepared by crosslinking N-isopropylacrylamide (NPIAAm) and sodium carboxymethylcellulose (CMC) by ultraviolet irradiation in the presence of a photoinitiator and a crosslinker. At 20°C, 0.8 g of monomer NIPAAm, 0.03 g of α-ketoglutaric acid and 0.02 g of N, N-methylenebisacrylamide were dissolved in 10 mL of deionized water, and then 0.06 g of sodium carboxymethylcellulose was added to the above solution, magnetically stirred for 4 h, and the mixed solution was slowly injected into a 6 cm culture dish, and the culture dish was moved to a sealed container, N2 was introduced for 20 min, and then placed under a 250 W ultraviolet lamp for 40 min to obtain a large-pore core layer hydrogel, which was then soaked in deionized water for 24 h, and the water was changed regularly to remove unreacted monomers and crosslinkers.
[0035] Step 2: Preparation of core-shell structure PAAS-PNIPAAm hydrogel 2.0g monomer acrylic acid (AA), 0.05g α-ketoglutaric acid and 0.1g N, N-methylenebisacrylamide were dissolved in 10mL of dimethyl sulfoxide-water (DMSO-H2O) mixed solution. The mixed aqueous solution was then injected into the mold, and then the mold was slowly moved into a sealed container, N2 was passed through for 20min, and then placed in a 250W UV light box for irradiation for 20min. The core-shell structure hydrogel was carefully removed from the mold and soaked in deionized water for 24h until the unreacted monomers and dimethyl sulfoxide were removed.
[0036] Step 3: Preparation of core-shell PAAS-PNIPAAm hydrogel materials for environmental water collection
[0037] First, 1L pH = 8.5, 50mM Tris-HCl buffer solution was prepared, and then the dried core-shell structure PAAS-PNIPAAm hydrogel was added to the buffer solution. After fully swelling for 24 hours, the sample was immersed in a Tris-HCl buffer solution containing 2mg / mL dopamine and 5mM CuSO4 / 19.6mM H2O2 again, and magnetically stirred for 4 hours. Subsequently, the sample was washed with water overnight and placed in a freeze dryer for pre-freezing and freeze drying to obtain dopamine-modified PAAS-PNIPAAm hydrogel. Finally, it was immersed in 100mL of LiCl solution with a concentration of 0.1g / mL for 24 hours, and the prepared PAAS-PNIPAAm hydrogel modified with polydopamine and lithium chloride was dried in an oven at 80°C for 3 days.
[0038] The surface condition of the core-shell PAAS-PNIPAAm hydrogel material for environmental water collection prepared in this embodiment can be found in Figure 3 .like Figure 3As shown, the core layer PNIPAAm hydrogel and the shell layer PAAS hydrogel are tightly combined, and core-shell hydrogels with large and small pore sizes are successfully synthesized.
[0039] The hydrophilic surface of the core-shell PAAS-PNIPAAm hydrogel material for environmental water collection prepared in this example can be found in Figure 4 .like Figure 4 As shown, the surface of the material prepared in this embodiment has water droplets completely absorbed within 135 ms, and has good hydrophilic properties.
[0040] Comparative Example 1
[0041] This comparative example prepares a PNIPAAm environmental water collection material according to the following steps:
[0042] Step 1: Preparation of PNIPAAm hydrogel
[0043] At 20°C, 0.8 g of monomer NIPAAm, 0.03 g of α-ketoglutaric acid and 0.02 g of N,N-methylenebisacrylamide were dissolved in 10 mL of deionized water, and then 0.06 g of sodium carboxymethyl cellulose was added to the solution and magnetically stirred for 4 h. The mixed solution was slowly injected into a 6 cm culture dish, and the culture dish was moved to a sealed container. After N2 was introduced for 20 min, it was placed under a 250 W ultraviolet lamp for irradiation for 40 min to obtain a large-pore core layer hydrogel, which was then soaked in deionized water for 24 h, and the water was changed regularly to remove unreacted monomers and cross-linking agents.
[0044] Step 2: Preparation of PNIPAAm environmental water collection materials
[0045] 1L of pH=8.5, 50mM Tris-HCl buffer solution was prepared, and then the PNIPAAm hydrogel was added to the buffer solution. After sufficient swelling for 24h, the sample was immersed in a Tris-HCl buffer solution containing 2mg / mL dopamine and 5mM CuSO4 / 19.6mM H2O2 again and magnetically stirred for 4h. Subsequently, the sample was washed with water overnight and placed in a freeze dryer for pre-freezing and freeze-drying to obtain polydopamine-modified PNIPAAm hydrogel. Finally, it was immersed in 100mL of 0.1g / mL LiCl solution for 24h. The prepared polydopamine and lithium chloride-modified PNIPAAm hydrogel was dried in an oven at 80℃ for 3 days.
[0046] The surface condition of a PNIPAAm environmental water collection material prepared in this comparative example can be found in Figure 2 , Figure 2 This is a SEM image of the surface of the PNIPAAm environmental water collection material prepared in Comparative Example 1. Figure 2As shown, PNIPAAm hydrogel has a larger pore structure.
[0047] Comparative Example 2
[0048] This comparative example prepares the PAAS hydrogel environmental water collection material according to the following steps:
[0049] Step 1: Preparation of PAAS hydrogel
[0050] 2.0g monomer acrylic acid, 0.05g α-ketoglutaric acid and 0.1g N, N-methylenebisacrylamide were dissolved in 10mL of dimethyl sulfoxide-water (DMSO-H2O) mixed solution. Then the mixed solution was injected into a culture dish, and then the culture dish was slowly moved to a sealed container, N2 was passed through for 20min, and then placed in a 250W UV light box for irradiation for 20min. The obtained PAAS hydrogel was carefully removed from the mold and soaked in deionized water for 24h until the unreacted monomer and dimethyl sulfoxide were removed.
[0051] Step 2: Preparation of PAAS hydrogel environmental water collection materials
[0052] Prepare 1L pH=8.5, 50mM Tris-HCl buffer solution, then add PAAS hydrogel to the buffer solution, fully swell for 24h, and then immerse the sample again in Tris-HCl buffer solution containing 2mg / mL dopamine and 5mM CuSO4 / 19.6mM H2O2, magnetically stir for 4h, then wash the sample with water overnight and place it in a freeze dryer for pre-freezing and freeze drying to obtain polydopamine-modified PAAS hydrogel, and finally immerse it in 100mL of 0.1g / mL LiCl solution for 24h. The prepared polydopamine and lithium chloride-modified PAAS hydrogel was dried in an oven at 80℃ for 3 days.
[0053] The surface condition of a PAAS hydrogel environmental water collection material prepared in this comparative example can be found in Figure 1 , Figure 1 This is a SEM image of the surface of the PAAS hydrogel environmental water collection material prepared in Comparative Example 2. Figure 1 As shown, PAAS hydrogel has a smaller pore size structure.
[0054] In summary, the present invention discloses a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection. This method is more environmentally friendly than the existing preparation technology, and the process is simple and easy to operate. It solves the problems of poor hygroscopic performance, low water collection efficiency, and water evaporation in a low-humidity environment. While ensuring that the material has good hygroscopic properties, it has excellent photothermal conversion performance and water release performance, which greatly improves the water collection efficiency. Therefore, this material can provide a promising solution for clean water production in arid and inland / remote areas.
[0055] It should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection, characterized in that: The method comprises the following steps: firstly preparing a core layer poly N-isopropylacrylamide macroporous hydrogel by ultraviolet irradiation method, then coating a layer of sodium polyacrylate hydrogel with small pore size and open pore structure on the surface of the poly N-isopropylacrylamide hydrogel to obtain sodium polyacrylate-poly N-isopropylacrylamide hydrogel, finally coating polydopamine nanoparticles on the surface of the sodium polyacrylate-poly N-isopropylacrylamide hydrogel, immersing the hydrogel in a LiCl solution for 24 hours, drying the prepared hydrogel with core-shell structure in an oven at 80°C for 3 days, and obtaining a sodium polyacrylate-poly N-isopropylacrylamide hydrogel material with core-shell structure for environmental water collection.
2. A core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 1, characterized in that: The preparation process of the core layer poly N-isopropylacrylamide macroporous hydrogel is as follows: at 20°C, monomer N-isopropylacrylamide, photoinitiator α-ketoglutaric acid and crosslinker N,N-methylenebisacrylamide are dissolved in 10 mL of deionized water, then sodium carboxymethylcellulose is added to the solution, and magnetic stirring is performed for 4 hours to obtain a mixed aqueous solution of N-isopropylacrylamide, the uniformly mixed solution is slowly injected into a 6 cm culture dish, and the culture dish is moved to a sealed container, N2 is introduced for 20 minutes, and then irradiated under a 250 W ultraviolet lamp for 40 minutes, and soaked in deionized water for 24 hours, and the water is changed regularly to remove unreacted monomers and crosslinkers.
3. A core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 2, characterized in that: The mass concentration of the required monomer N-isopropyl acrylamide is 2% to 10%; the mass concentration of the crosslinking agent is 1% to 5%; the mass concentration of the sodium carboxymethyl cellulose is 0.1% to 1%; and the mass concentration of the photoinitiator is 0.5%.
4. The core-shell PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 2, characterized in that: The preparation process of the sodium polyacrylate-poly N-isopropylacrylamide hydrogel is as follows: first, monomer acrylic acid, photoinitiator α-ketoglutaric acid and crosslinking agent N, N-methylenebisacrylamide are dissolved in a dimethyl sulfoxide-water mixed solution, and then the mixed solution is injected into a mold, and then the mold is slowly moved into a sealed container, N2 is introduced for 20 minutes, and then placed in a 250W ultraviolet lamp for irradiation for 20 minutes, and the obtained core-shell structure hydrogel is carefully taken out from the mold and immersed in deionized water for 24 hours until the unreacted monomer and dimethyl sulfoxide are removed.
5. A core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 4, characterized in that: The required monomer acrylic acid mass concentration is 0.5% to 3%; the mass concentration of the cross-linking agent is 2% to 12%; the volume ratio of dimethyl sulfoxide to water is 1:9 to 1:1; and the mass concentration of the photoinitiator is 0.5%.
6. The core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 4, characterized in that: First, a sodium polyacrylate-poly N-isopropylacrylamide hydrogel is prepared according to the requirements of claim 4, and then the sodium polyacrylate-poly N-isopropylacrylamide hydrogel is added to a pH=8.5, 50mM Tris-HCl buffer solution. After fully swelling for 24 hours, the sample is immersed in a Tris-HCl buffer solution containing dopamine and 5mM CuSO4 / 19.6mM H2O2 again, and magnetically stirred for 4 hours. Subsequently, the sample is washed with water overnight and placed in a freeze dryer for pre-freezing and freeze-drying to obtain a sodium polyacrylate-poly N-isopropylacrylamide hydrogel modified with polydopamine. Finally, it is immersed in a LiCl solution for 24 hours. The prepared sodium polyacrylate-poly N-isopropylacrylamide hydrogel modified with polydopamine and lithium chloride is dried in an oven at 80°C for 3 days to obtain a core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection.
7. A core-shell structure PAAS-PNIPAAm hydrogel material for environmental water collection according to claim 6, characterized in that: The dopamine concentration is 2-10 mg / mL; the LiCl solution concentration is 0.1-0.6 g / mL.
Citation Information
Patent Citations
MOFs material with efficient water collection performance, preparation method of MOFs material and application of MOFs material to water extraction from air
CN113426416A
Natural polymer-based atmospheric water collecting material and preparation method thereof
CN113501995A